Nutrient deficiencies for the irrigated rice in succession to the bean plant in lowland soil - Andrade, Wander Eustáquio de Bastos; Souza, Augusto Ferreira de; Carvalho, Janice Guedes de (Pesquisa Agropecuaria Brasileira, 1998)
This study aimed at evaluating the response in bean-rice rotation related to liming application and macro and micronutrients fertilization. This experiment was conducted in a greenhouse, in an organic soil from the Northern Fluminense region. The following treatments to bean plants were considered: control (natural soil), "complete" (N, P, K, limestone, S, B, Co, Cu, Mo, and Zn) and "complete" but one by one of the related nutrients. The experimental design was a randomized block with four replications. After the bean harvest, rice seeds were planted in the same previous soil used (pots), adding N, P and K according to recommendations. The effect of treatments was measured by dry matter production considering plant shoot and nutrient accumulation. Only the control treatment and the others without N or K showed a significant decrease in the dry matter production in comparison to the "complete" treatment, such as 59, 49 and 38% for the control treatment and the treatments without N and K, respectivelly. The nutrient accumulation by the aerial part of the rice occured on the following arrangement: N>K>Ca>P>Mg>S>Fe>Mn>Zn>Cu>B.